2015
DOI: 10.1259/dmfr.20140223
|View full text |Cite
|
Sign up to set email alerts
|

The reduction of dose in paediatric panoramic radiography: the impact of collimator height and programme selection

Abstract: Panoramic systems when used to frequently image children should have programmes specifically designed for imaging small heads. There should be a shorter collimator available and programmes that deliver a reduced exposure time and allow reduction of tube current. Programme selection should also provide flexibility for focal trough size, shape and position to match the smaller head size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
0
13
0
7
Order By: Relevance
“…These values are slightly higher than measurements found in other studies using the Rando adult phantoms and TLDs [6,[17][18][19][20][21]. In a study by Davis et al, [22] the effective dose measured using a short collimator was 7.7 microsieverts.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These values are slightly higher than measurements found in other studies using the Rando adult phantoms and TLDs [6,[17][18][19][20][21]. In a study by Davis et al, [22] the effective dose measured using a short collimator was 7.7 microsieverts.…”
Section: Discussionmentioning
confidence: 60%
“…A study done by Davis et al, found that a short collimator should be used, and settings should produce a reduced exposure time and allow for reduction of tube current. Protocol selection should also provide flexibility for focal trough size, shape, and position to match the smaller head size [22]. A study done by Hayakawa et al, found that when lower kVp or mA settings were used for the Orthophos P10 and the PM 2002 CC panoramic units, absorbed doses were effectively reduced for all combinations of machines, programs, and detectors [9].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reported that diagnostic X-rays may increase the incidence of leukaemia and brain cancer and may have the potential to trigger the onset of any type of cancer in children 3 . Even if the expected amount of radiation is minor in dental panoramic radiography, efforts to apply it carefully and to reduce the dose are essential for paediatric patients 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…1 During dental panoramic tomography of children, a dose reduction of 20-40% can be achieved through segmented programmes, and a dose reduction of 57% to the brain and 41% to the eyes can be achieved by vertical field size reduction. 2,3 Reduction of image size is an easy, achievable and useful way to minimize the radiation dose of the radiosensitive organs that are located in the maxillomandibular area.…”
Section: Introductionmentioning
confidence: 99%